Neurociências e a prática docente no processo de aprendizagem da leitura das crianças do 1º ciclo do ensino fundamental - Oliveira, Mylena Perpétua dos Santos (Brasil, 2024)
The present study aimed to understand how knowledge of the neurobiological foundations of reading can influence the pedagogical practices of teachers in the 1st cycle of elementary education in a public school in the municipality of Parintins, Am. To achieve the proposed objective, the research adopted a qualitative descriptive approach. Data collection was done through semi-structured interviews conducted with two teachers working in this grade level. The results obtained reveal that the teachers have limited knowledge about neuroscience and its implications in the learning process of reading. Therefore, it is necessary to invest in continuous teacher training, as well as in didactic-pedagogical strategies that can be used to facilitate the learning process of reading for children based on neuroscience. It is believed that investing in teacher education can enhance the pedagogical practices of teachers, contributing to the development of children's reading skills. Additionally, it is hoped that this research can arouse the interest of other professionals in the importance of neuroscience in the field of education, encouraging further studies and reflections on the topic.